IMPLEMENTATION OF DIGITAL MARKETING FOR MARKETING AND SELLING VALUE OF UMKM PRODUCTS IN BITUNG JAYA VILLAGE, CIKUPA, TANGRANG REGENCY - Ali Fikri, Muhamad Agung; Ahmad Fauji; Beby Tiara; Yulis Nuryanti (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2025)
The Community Service Program aims to educate participants on how to increase product sales and marketing value through digital marketing. The UNIPI PKM team, comprised of lecturers and students, visited the location and delivered relevant information and education to participants through visual and interactive methods. The program concluded with a Q&A session, evaluation, and documentation. The digital marketing training, conducted through the use of technology, can be applied by participants in marketing MSME products efficiently and effectively.